Development of Electronic Student Worksheets (E-LKPD) Pendap Bengkulu Based on Discovery Learning as A Learning Media for Additive Material - Putri Nutriastuti; Mellyta Uliyandari; Deni Parlindungan; Afrizal Mayub; Aprina Defianti (Universitas Pendidikan Mandalika, 2024)
This research aims to develop the electronic student worksheets (E-LKPD) Pendap Bengkulu based on Discovery Learning as a Learning Media for Additive Material in Science lesson content for class VIII SMP. This study used the 4D development model (Define, Design, Develop, and Disseminate), which was limited to the development stage with limited trials conducted at SMPN 03 Bengkulu City, with a sample of 33 students from class VIII.1. To collect data, several questionnaires were distributed to media experts, material experts, participants, and students. Data analysis was carried out using descriptive statistical analysis techniques using percentage analysis. The results of the research showed that the feasibility test of E-LKPD involving 3 material experts, 2 media experts, and 2 participants resulted in an 92.3% percentage of validation test results, and it can be said that E-LKPD Pendap Bengkulu, which was developed as a learning medium for additive material for junior high school students, was very feasible to use. Analysis of student readability of E-LKPD Pendap Bengkulu as a learning medium for additive material for junior high school students resulted in a percentage of 89.8% readability response, indicating that E-LKPD is very well applied to junior high school students in grade VIII.